New Waves, Paradigms, and Theory: Moving Public Engagement Forward - Trina Van Schyndel (The University of Alabama, 2022)
Review of the book: Margaret A. Post, Elaine Ward, Nicholas V. Longo, and John Saltmarsh (Eds.), Publicly Engaged Scholars: Next-Generation Engagement and the Future of Higher Education. Sterling, VA: Stylus Publishing, 2016, 312 pages. ISBN: 978-1-62036-264-8